Advances in Contactless Silicon Defect and Impurity Diagnostics Based on Lifetime Spectroscopy and Infrared Imaging. (31st May 2007) - Schmidt, Jan; Pohl, Peter; Bothe, Karsten; Brendel, Rolf
Abstract : This paper gives a review of some recent developments in the field of contactless silicon wafer characterization techniques based on lifetime spectroscopy and infrared imaging. In the first part of the contribution, we outline the status of different lifetime spectroscopy approaches suitable for the identification of impurities in silicon and discuss—in more detail—the technique of temperature- and injection-dependent lifetime spectroscopy. The second part of the paper focuses on the application of infrared cameras to analyze spatial inhomogeneities in silicon wafers. By measuring the infrared signal absorbed or emitted from light-generated free excess carriers, high-resolution recombination lifetime mappings can be generated within seconds to minutes. In addition, mappings of non-recombination-active trapping centers can be deduced from injection-dependent infrared lifetime images. The trap density has been demonstrated to be an important additional parameter in the characterization and assessment of solar-grade multicrystalline silicon wafers, as areas of increased trap density tend to deteriorate during solar cell processing.